Nanomaterials for detection of primary aromatic amine derivatives based on a fluorescent probe. (12th June 2020) - Lee, Yu Jeong; Kang, In Soo; Shin, Yo Seob; Lee, Seung Woo
Abstract: The fluorescent trans -styrylbenzene with an aldehyde moiety as the biding site, ( E )-4-styrylbenzaldehyde, was synthesized and the chemical structure was measured by 1 H nuclear magnetic resonance (NMR) spectroscopy and Fourier transform infrared (FTIR) spectroscopy. The capability of the molecule as a chemosensor for aniline and 4-nitroaniline was examined using FTIR spectroscopy and fluorescence spectroscopy. Both aniline and 4-nitroaniline formed imine groups by a reaction with ( E )-4-styrylbenzaldehyde. On the other hand, the ( E )-4-styrylbenzaldehyde molecule recognized only 4-nitroaniline with high selectivity. Silica nanoparticles (SNPs), which have fluorescent trans -styrylbenzene with the aldehyde moiety on the surface, SBA-SNP, was prepared using a modified Stöber synthetic method. The prepared SBA-SNP was characterized by field emission scanning electron microscopy, FTIR spectroscopy, and fluorescence spectroscopy. The SBA-SNP had a spherical shape with a mean diameter of 150 nm. The SBA-SNP recognized only the 4-nitroaniline molecule with high selectivity through fluorescence quenching in emission, and the pale green fluorescence color disappeared with increasing concentration of 4-nitroaniline.